Human and environmental security an agenda for change (London Earthscan, 2005)
Security has tended to be seen as based on military force, yet this illusion is crumbling, literally and figuratively, before our eyes in the conflict zones of Iraq, Afghanistan and Africa. It is now clear that real human security, defined by the Commission on Human Security as 'protecting vital freedoms', can only be achieved if the full range of issues that underpin human security - including environmental integrity - are addressed. This ground-breaking book, authored by prominent international decision makers, tackles the global human security problem across the range of core issues including terrorism, nuclear proliferation, access to water, food security, loss of biodiversity and climate change. The authors identify the causes of insecurity, articulate the linkages between the different elements of human security and outline an agenda for engaging stakeholders from across the globe in building the foundations of genuine and lasting human security for all nations and all people. This is powerful, necessary, solution-focused reading in these times of peril, global conflict, mass inequity and rampant environmental degradation.
Includes index
Keywords: Security, International